Towards the semiotic and the symbolic in music theory and analysis: Kristeva’s dialectics as a model for plurality in metadiscursive and discursive engagements with music - Potgieter, Zelda (University of the Free State, 2013)
This article examines both metadiscursive and discursive theoretical and analytical engagements with musical experience from the perspective of Julia Kristeva’s distinction between semiotic and symbolic signifying dispositions, and the dialectic in which they are poised, as these are set out in Revolution in poetic language (1984), in particular. To this end analyses of the Beethoven and Schubert settings of the character Mignon’s first song in Goethe’s Wilhelm Meisters Lehrjahre are offered, focusing on selected analytical approaches deemed to represent symbolic and semiotic dispositions, respectively, which, in turn, expose aspects of transposition or intertextuality. In this manner, a model for long-debated notions of heterodoxy and plurality in the practice of music theory and analysis is suggested.
Keywords: Revolution in poetic language (1984); Wilhelm Meisters Lehrjahre; Kristeva, Julia; Goethe, Johann Wolfgang von